Náttúra by Kitchen Theory: An immersive multisensory dining concept - Youssef, J; Spence, C (Elsevier, 2021)
The Náttúra dining concept developed by Kitchen Theory ran from September to December 2014 in London. It was inspired by the New Nordic Cuisine Manifesto which has influenced not only cuisine in the Nordic countries but international gastronomy more broadly for a number of years now. This multisensory dining concept incorporated dishes that have subsequently appeared in peer-reviewed academic research, including in this journal, thus highlighting the potential of practice-led gastrophysics research (as in research that was designed to optimize the eye-appeal of the plating of one of the dishes served on the menu). By incorporating different nature/natural sounds with each pair of courses (namely the sounds of the earth, wind, fire, and water), this multisensory dining concept bridges the contemporary interest in ‘sonic seasoning’ and the increasingly common approach of incorporating atmospheric soundscapes into gastronomic dining experiences. At the same time, nature videos projected onto the wall of the dining room, together with the use of atmospheric ambient aromas incorporated into several of the dishes further helped to transport guests to a range of different immersive multisensory environments, all loosely connected by an Icelandic theme.